Cu(III)-Mediated Aerobic Oxidations - Esguerra, Kenneth Virgel N.; Lumb, Jean-Philip (Synthesis, 2019)
CuIII species have been invoked in many copper-catalyzed transformations including cross-coupling reactions and oxidation reactions. In this review, we will discuss seminal discoveries that have advanced our understanding of the CuI/CuIII redox cycle in the context of C–C and C–heteroatom aerobic cross-coupling reactions, as well as C–H oxidation reactions mediated by CuIII–dioxygen adducts.1 General Introduction2 Early Examples of CuIII Complexes3 Aerobic CuIII-Mediated Carbon–Heteroatom Bond-Forming Reactions4 Aerobic CuIII-Mediated Carbon–Carbon Bond-Forming Reactions5 Bioinorganic Studies of CuIII Complexes from CuI and O25.1 O2 Activation5.2 Biomimetic CuIII Complexes from CuI and Dioxygen5.2.1 Type-3 Copper Enzymes and Dinuclear Cu Model Complexes5.2.2 Particulate Methane Monooxygenase and Di- and Trinuclear Cu Model Complexes5.2.3 Dopamine–β-Monooxygenase and Mononuclear Cu Model Complexes6 Conclusion
Keywords: Cu(III) oxidation; copper–oxygen complexes; biomimetic Cu(III) species; aerobic oxidations